A gradient structure transversal perovskite solar cell and a preparation method thereof
Patent Information
- Application Number
- CN202610822530.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-06-09
AI Technical Summary
然而,二维钙钛矿层自身导电性较差、载流子迁移率低,易形成电荷传输势垒;且二维相与三维相的能级匹配、取向控制与相纯度难以精准调控,易造成短路电流与填充因子损失;
[0013]采用上述技术方案后,本发明一种高效稳定的梯度结构反式钙钛矿太阳能电池及制备方法,具有以下有益效果:与传统三维二维复合结构钙钛矿太阳能电池相比,本发明利用反式电池骨架结构特点,可以完整保留填充在介观结构绝缘框架层中FAPbI3三维钙钛矿光吸收层,同时,将填充在介观结构电子传输层中FAPbI3层位于上侧的1/3~1/2区域转化为厚度足够的二维钙钛矿,既能充分利用二维钙钛矿层提升稳定性,又不阻碍电子提取传输,这种三维二维梯度结构可保证反式钙钛矿太阳能电池获得高光电转换效率和良好的长期稳定性。
Smart Images

Figure CN122396148B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and in particular to a gradient structure inverted perovskite solar cell and its fabrication method. Background Technology
[0002] Perovskite solar cells, as a new generation of high-efficiency, low-cost photovoltaic technology, have developed rapidly in recent years, with photoelectric conversion efficiency improving rapidly and possessing the potential for large-scale industrialization. Organic-inorganic hybrid three-dimensional perovskite materials, represented by formicinium triiodolead(II)ate (FAPbI3), have good light absorption and carrier transport properties, but their intrinsic stability is poor, and they are sensitive to water, oxygen, light, and thermal stress, and are prone to phase transitions and decomposition. At the same time, the high density of defects on the thin film surface and at grain boundaries leads to severe nonradiative recombination and ion migration, which limits the efficiency and lifespan of the devices.
[0003] To address these issues, the industry often employs two-dimensional perovskites to modify and passivate the interface of three-dimensional perovskites. Utilizing the hydrophobic properties and defect passivation of two-dimensional perovskites, water and oxygen erosion can be effectively blocked, surface dangling bonds filled, and carrier recombination and ion migration suppressed, thereby improving device stability and open-circuit voltage. However, two-dimensional perovskite layers themselves have poor conductivity and low carrier mobility, easily forming charge transport barriers; furthermore, the energy level matching, orientation control, and phase purity of the two-dimensional and three-dimensional phases are difficult to precisely regulate, easily leading to short-circuit current and fill factor loss. In addition, the organic ligands have weak binding force and are prone to desorption and degradation. The uniformity and coverage of the interface modification layer are difficult to guarantee, resulting in the device performance consistency and long-term reliability still failing to meet the needs of practical applications.
[0004] Therefore, developing a novel three-dimensional and two-dimensional gradient structure perovskite light absorption layer that can fully utilize the excellent properties of three-dimensional and two-dimensional perovskites while overcoming their defects is an effective way to obtain efficient and stable perovskite solar cells.
[0005] In view of this, after in-depth research, this case came into being. Summary of the Invention
[0006] The purpose of this invention is to provide a highly efficient and stable gradient structure inverted perovskite solar cell.
[0007] Another objective of this invention is to provide a method for preparing a highly efficient and stable gradient structure inverted perovskite solar cell.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A gradient structure inverted perovskite solar cell includes a conductive glass conductive layer, and a planar hole transport layer, an insulating frame layer, and an electron transport layer sequentially stacked on the conductive glass conductive layer. The hole transport layer is a planar structure hole transport layer, the insulating frame layer is a mesoscopic structure insulating frame layer, and the electron transport layer is a mesoscopic structure electron transport layer. The planar structure hole transport layer, the mesoscopic structure insulating frame layer, and the mesoscopic structure electron transport layer together constitute the inverted cell framework. FAPbI3 three-dimensional perovskite is filled in the inverted battery skeleton; the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer filled in the electron transport layer is transformed into two-dimensional perovskite to form a three-dimensional two-dimensional gradient structure perovskite light absorption layer. The three-dimensional two-dimensional gradient structure perovskite light absorption layer is a FAPbI3 / (PEA)2PbI4 three-dimensional two-dimensional gradient structure perovskite light absorption layer. An AZO top electrode is sputtered onto the electron transport layer to obtain a gradient structure inverted perovskite solar cell.
[0009] Furthermore, the hole transport layer is prepared from NiO nanocrystal particles of 3-5 nm, and the hole transport layer is a NiO nanocrystal hole transport layer. The mesoscopic insulating framework layer is prepared from ZrO2 mesoporous hollow microspheres of 100-200 nm. The electron transport layer is prepared from SnO2 nanorods of 2-4 nm in diameter and aspect ratio of 3-5 through self-assembly to form 100-250 nm mesoporous microspheres, and the electron transport layer is a SnO2 nanorod electron transport layer.
[0010] Furthermore, the three-dimensional two-dimensional gradient perovskite light-absorbing layer is replaced by organic large cations in the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer within the electron transport layer. + Ions generate a two-dimensional perovskite, which forms a gradient structure with the FAPbI3 three-dimensional perovskite filling the insulating framework layer.
[0011] Furthermore, the organic macrocation is phenylethylammonium or 4-fluorophenylethylammonium.
[0012] A method for fabricating a gradient structure inverted perovskite solar cell as described above includes the following steps: Step 1: Prepare a 1.5-5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 180-200℃ for 6-12 hours, cool it naturally to room temperature, centrifuge it at 6000-10000 rpm for 15-30 minutes, collect the centrifuged material, and obtain 100-200 nm ZrO2 mesoporous hollow microspheres; Step 2: Disperse SnO2 nanorods with a particle size of 2-4 nm, an aspect ratio of 3-5, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 5-10 mg / mL. Using a high-shear emulsifier with stirring at 10,000 to 20,000 rpm, 4 to 10 times the volume of the ethanol / isopropanol antisolvent is added dropwise to the dispersion to aggregate SnO2 nanorods and form microsphere precipitates. The volume ratio of ethanol to isopropanol in the ethanol / isopropanol antisolvent is 1:1 to 1:4. Centrifuge at 4000-8000 rpm for 15-30 minutes and collect the centrifuged material; add 5-10 times the volume of the centrifuged material in NOBF4 acetonitrile solution, wherein the NOBF4 concentration of the NOBF4 acetonitrile solution is 5-10 mg / mL, and let stand for 12-24 hours to remove the oleamine ligands on the surface of SnO2 nanorods, further agglomerating the nanorods to form stable mesoporous microspheres; then centrifuge at 4000-8000 rpm for 15-30 minutes and collect the centrifuged material to obtain 100-150 nm SnO2 mesoporous microspheres. Step 3: Disperse NiO nanocrystals with an oil amine ligand and a particle size of 3-5 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2-8 mg / mL. The dispersion was spin-coated onto the conductive layer of conductive glass in two steps. First, the dispersion was spin-coated at 400-800 rpm for 5-10 seconds to allow it to spread and wet the conductive layer. Then, the dispersion was spin-coated at 3000-5000 rpm for 30-60 seconds to control the thickness of the NiO nanocrystalline particle layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Step 4: Disperse the ZrO2 mesoporous hollow microspheres with a particle size of 100~200 nm prepared in Step 1 in anhydrous ethanol / isopropanol with a volume ratio of 1:1~5:1 to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 100~250 mg / mL. The dispersion was spin-coated onto the NiO nanocrystalline particle layer in two steps. First, the dispersion was spin-coated at 400-800 rpm for 5-15 seconds to allow it to spread fully. Then, the dispersion was spin-coated at 1500-3000 rpm for 30-60 seconds to control the thickness of the ZrO2 mesoporous hollow microsphere layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Step 5: Disperse the SnO2 mesoporous microspheres with a particle size of 100~150 nm prepared in step 2 in anhydrous ethanol / isopropanol with a volume ratio of 1:1~5:1 to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 100~150 mg / mL. The dispersion was spin-coated onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method. First, the dispersion was spin-coated at 400-800 rpm for 5-15 seconds to allow it to spread fully. Then, the dispersion was spin-coated at 3000-5000 rpm for 30-60 seconds to control the thickness of the SnO2 mesoporous microsphere layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Finally, the sample was sintered in an air atmosphere at 400-500 °C for 30-60 minutes to obtain an inverted battery skeleton in which a hole transport layer, a ZrO2 insulating framework layer, and an electron transport layer were sequentially stacked on a conductive glass conductive layer. The hole transport layer had a thickness of 15-25 nm, the ZrO2 insulating framework layer had a thickness of 0.5-1 μm, and the electron transport layer had a thickness of 300-500 nm. Step 6: At a rotation speed of 8000~12000 rpm, spin-coat the FAPbI3 perovskite light-absorbing layer precursor solution into the mesopores of the ZrO2 insulating framework layer and electron transport layer within the inverted battery framework prepared in Step 5. Dissolve phenylethylammonium or 4-fluorophenylethylammonium organic macrocations in chlorobenzene. During the spin-coating antisolvent-induced crystallization process, FA in the upper 1 / 3~1 / 2 region of the FAPbI3 layer within the electron transport layer... + Ion substitution followed by annealing at 100-150 °C for 10-30 minutes yields a three-dimensional two-dimensional gradient perovskite light-absorbing layer with FAPbI3 / (PEA)2PbI4 structure. Finally, an AZO top electrode was sputtered onto the electron transport layer to obtain a gradient structure inverted perovskite solar cell.
[0013] After adopting the above technical solution, the present invention provides a highly efficient and stable gradient structure inverted perovskite solar cell and its preparation method, which has the following beneficial effects: Compared with traditional three-dimensional and two-dimensional composite perovskite solar cells, the present invention utilizes the characteristics of the inverted cell framework structure to completely retain the FAPbI3 three-dimensional perovskite light absorption layer filled in the mesoscopic insulating framework layer. At the same time, the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer filled in the mesoscopic electron transport layer is transformed into a two-dimensional perovskite with sufficient thickness. This not only makes full use of the two-dimensional perovskite layer to improve stability, but also does not hinder electron extraction and transport. This three-dimensional and two-dimensional gradient structure can ensure that the inverted perovskite solar cell obtains high photoelectric conversion efficiency and good long-term stability.
[0014] In the field of inverted perovskite solar cells, constructing two-dimensional / three-dimensional heterojunctions is one of the important strategies for improving device stability. However, in existing methods, two-dimensional perovskite layers are usually only used as extremely thin interface modification layers. Due to the poor intrinsic conductivity and low carrier mobility of two-dimensional perovskite, this thin layer, while passivating defects, still forms a charge transport barrier, causing some photogenerated carriers to be blocked, thus limiting further improvement in the photoelectric conversion efficiency of the device.
[0015] If attempts are made to thicken the two-dimensional perovskite layer in order to fundamentally improve the long-term operational stability of the device by utilizing its excellent material stability, the transport barrier of the two-dimensional layer itself will be significantly aggravated, leading to a sharp decrease in short-circuit current density and fill factor. Therefore, under the current technology system, there is a fundamental contradiction between the "thickness" and "charge transport efficiency" of the two-dimensional perovskite layer: thin layers cannot provide sufficient stability gain, while thick layers severely sacrifice efficiency. How to overcome this contradiction and enable the device to simultaneously achieve high photoelectric conversion efficiency and excellent long-term stability is a long-standing and unsolved technical problem in this field.
[0016] This invention innovatively constructs a planar hole transport layer, a mesoscopic ZrO2 insulating framework layer, and a mesoscopic electron transport layer sequentially stacked on a conductive glass conductive layer, and then sintersects in an air atmosphere at 400-500 °C for 30-60 minutes to obtain an inverted battery framework composed of a high-quality planar hole transport layer, a mesoscopic ZrO2 insulating framework layer, and a mesoscopic electron transport layer. Utilizing the structural characteristics of this inverted battery framework, the three-dimensional FAPbI3 light-absorbing layer filled in the mesoscopic insulating framework layer can be completely preserved. Simultaneously, the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer in the mesoscopic electron transport layer is transformed into a two-dimensional perovskite layer with a thickness of 100-250 nm, which is 10 times the thickness of the two-dimensional perovskite in traditional two-dimensional / three-dimensional perovskite devices, thus fundamentally improving device stability. Meanwhile, the unconverted portion of FAPbI3 in the mesoscopic electron transport layer can fully contact the electron transport layer, forming a good electron transport channel and achieving high photoelectric conversion efficiency.
[0017] This ingenious device structure design can make full use of the two-dimensional perovskite layer to improve stability without hindering electron extraction and transport. This three-dimensional two-dimensional gradient structure can ensure that the inverted perovskite solar cell achieves high photoelectric conversion efficiency and good long-term stability. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the battery structure of the present invention. In the picture: FTO is a conductive layer of conductive glass (fluorine-doped SnO2 conductive glass). HTL is a planar hole transport layer (prepared from NiO nanocrystals). 3D PVK is a FAPbI3 perovskite light-absorbing layer filled within the battery skeleton; 2D PVK is a two-dimensional perovskite light-absorbing layer (converted from the upper 1 / 3 to 1 / 2 of the FAPbI3 layer filled in the mesoscopic electron transport layer). ZrO2 Mesoporous spheres are mesoscopic insulating framework layers prepared from ZrO2 mesoporous microspheres; SnO2Mesoporous spheres are mesoscopic electron transport layers prepared by self-assembling mesoporous microspheres from SnO2 nanorods. AZO is an aluminum-doped zinc oxide top electrode. Detailed Implementation
[0019] Example 1 I. Preparation This invention discloses a method for fabricating a gradient structure inverted perovskite solar cell, comprising the following steps: Step 1: Prepare a 2.5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 200℃ for 12 hours, cool it naturally to room temperature, centrifuge it at 8000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm ZrO2 mesoporous hollow microspheres.
[0020] Step 2: Disperse SnO2 nanorods with a particle size of 4 nm, an aspect ratio of 4, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 10 mg / mL. Using a high-shear emulsifier with stirring at 13,000 rpm, 8 times the volume of ethanol / isopropanol (volume ratio 1:1) antisolvent was slowly added dropwise to the dispersion to cause SnO2 nanorods to aggregate and form microsphere precipitates. The precipitate was then centrifuged at 6,000 rpm for 30 minutes and collected. Add 6 times the volume of the centrifuged material to a solution of nitrosotetrafluoroborate (NOBF4) acetonitrile (concentration 10 mg / mL), let stand for 24 hours to remove the oleamine ligands on the surface of the SnO2 nanorods, allowing the SnO2 nanorods to further aggregate and form stable mesoporous microspheres. Then centrifuge at 6000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm SnO2 mesoporous microspheres.
[0021] Step 3: Disperse NiO nanocrystals with an oil amine ligand and a particle size of 3.6 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2 mg / mL. The dispersion was spin-coated onto a conductive glass layer using a two-step spin-coating process. First, the dispersion was spin-coated at 500 rpm for 10 seconds to fully spread and wet the conductive glass layer. Then, it was spin-coated at 4000 rpm for 50 seconds to control the thickness of the NiO nanocrystalline particle layer. Afterward, it was dried at 100°C for 30 minutes. The conductive glass was a fluorine-doped SnO2 conductive glass.
[0022] Step 4: Disperse the ZrO2 mesoporous hollow microspheres with a particle size of 150 nm prepared in step 1 in anhydrous ethanol / isopropanol (volume ratio 1:1) to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 200 mg / mL. The dispersion was spin-coated onto the NiO nanocrystalline particle layer in step 3 using a two-step spin-coating process. First, the dispersion was spin-coated at 800 rpm for 10 s to allow it to spread fully. Then, it was spin-coated at 3000 rpm for 60 s to control the thickness of the ZrO2 mesoporous hollow microsphere layer. After that, it was dried by heating at 100 ℃ for 30 minutes.
[0023] Step 5: Disperse the SnO2 mesoporous microspheres with a particle size of 150 nm prepared in step 2 in anhydrous ethanol / isopropanol (volume ratio 1:1) to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 150 mg / mL. The dispersion was spin-coated onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method. First, the dispersion was spin-coated at 800 rpm for 5 seconds to allow it to spread fully, and then at 3000 rpm for 60 seconds to control the thickness of the SnO2 mesoporous microsphere layer. Then, place it at 100℃ for 30 minutes to dry; Finally, the sample was sintered at 450 °C in air for 60 minutes to obtain a planar hole transport layer (20 nm), a mesoscopic ZrO2 insulating framework layer (700 nm), and a mesoscopic electron transport layer (500 nm) sequentially stacked on a conductive glass conductive layer, which together constitute the inverted battery framework. The hole transport layer is a NiO nanocrystal hole transport layer, and the electron transport layer is a SnO2 nanorod electron transport layer.
[0024] Step 6: Prepare the FAPbI3 perovskite light absorption layer precursor solution [solute concentrations: formamidinium hydroiodide (FAI) 0.98 M, PbI2 1.08 M, formamidinium hydrochloride (FACl) 0.06 M; solvent: N,N-dimethylformamide / dimethyl sulfoxide, volume ratio 4:1. Spin-coat the FAPbI3 perovskite light absorption layer precursor solution into the mesopores of the ZrO2 insulating framework layer and the electron transport layer of the inverted battery framework prepared in Step 5 at a speed of 10,000 rpm until completely filled; A chlorobenzene solution of 3 mg / mL phenylethyl ammonium iodide (PEAI) was prepared. During a spin-coating process at 4000 rpm, the solution was dropped onto the mesoscopic electron transport layer filled with FAPbI3 precursor solution for 30 s, converting the upper half of the FAPbI3 filled in it into (PEA)2PbI4. Then, it was annealed at 150 °C for 20 min to generate a three-dimensional and two-dimensional gradient perovskite light absorption layer of FAPbI3 / (PEA)2PbI4, wherein the thickness of the three-dimensional perovskite of FAPbI3 is 800 nm and the thickness of the two-dimensional perovskite layer of (PEA)2PbI4 is 250 nm. After the sample was cooled to room temperature, anhydrous isopropanol was added dropwise at 6000 rpm for 10 s to completely remove the 2PbI4 two-dimensional perovskite layer covering the upper surface of the mesoscopic electron transport layer (PEA), so that the thickness of the exposed electron transport layer reached 50 nm. Finally, AZO was sputtered at low temperature to ensure that the upper surface of the electron transport layer was in full contact with the AZO electrode, thus obtaining a gradient structure inverted perovskite solar cell.
[0025] This invention provides a gradient structure inverted perovskite solar cell, such as... Figure 1 As shown, it includes a conductive glass conductive layer, and a planar hole transport layer, an insulating frame layer, and an electron transport layer sequentially stacked on the conductive glass conductive layer. The hole transport layer is a planar hole transport layer, the insulating frame layer is a mesoscopic insulating frame layer, and the electron transport layer is a mesoscopic electron transport layer. The planar hole transport layer, the mesoscopic insulating frame layer, and the mesoscopic electron transport layer together constitute a reverse battery skeleton. The FAPbI3 three-dimensional perovskite is filled in the inverted battery skeleton; the FAPbI3 layer filled in the electron transport layer is transformed into a two-dimensional perovskite in the upper 1 / 3 to 1 / 2 region (green area in the figure), forming a FAPbI3 / (PEA)2PbI4 three-dimensional two-dimensional gradient structure perovskite light absorption layer. An AZO top electrode (aluminum-doped zinc oxide top electrode) is sputtered onto the electron transport layer to obtain a gradient structure inverted perovskite solar cell.
[0026] After adopting the above technical solution, the present invention provides a highly efficient and stable gradient structure inverted perovskite solar cell and its preparation method, which has the following beneficial effects: Compared with traditional three-dimensional and two-dimensional composite perovskite solar cells, the present invention utilizes the characteristics of the inverted cell framework structure to completely retain the FAPbI3 three-dimensional perovskite light absorption layer filled in the mesoscopic insulating framework layer. At the same time, the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer filled in the mesoscopic electron transport layer is transformed into a two-dimensional perovskite with sufficient thickness. This not only makes full use of the two-dimensional perovskite layer to improve stability, but also does not hinder electron extraction and transport. This three-dimensional and two-dimensional gradient structure can ensure that the inverted perovskite solar cell obtains high photoelectric conversion efficiency and good long-term stability.
[0027] In the field of inverted perovskite solar cells, constructing two-dimensional / three-dimensional heterojunctions is one of the important strategies for improving device stability. However, in existing methods, two-dimensional perovskite layers are usually only used as extremely thin interface modification layers. Due to the poor intrinsic conductivity and low carrier mobility of two-dimensional perovskite, this thin layer, while passivating defects, still forms a charge transport barrier, causing some photogenerated carriers to be blocked, thus limiting further improvement in the photoelectric conversion efficiency of the device.
[0028] If attempts are made to thicken the two-dimensional perovskite layer in order to fundamentally improve the long-term operational stability of the device by utilizing its excellent material stability, the transport barrier of the two-dimensional layer itself will be significantly aggravated, leading to a sharp decrease in short-circuit current density and fill factor. Therefore, under the current technology system, there is a fundamental contradiction between the "thickness" and "charge transport efficiency" of the two-dimensional perovskite layer: thin layers cannot provide sufficient stability gain, while thick layers severely sacrifice efficiency. How to overcome this contradiction and enable the device to simultaneously achieve high photoelectric conversion efficiency and excellent long-term stability is a long-standing and unsolved technical problem in this field.
[0029] This invention innovatively constructs a planar hole transport layer, a mesoscopic ZrO2 insulating framework layer, and a mesoscopic electron transport layer sequentially stacked on a conductive glass conductive layer, and then sintersects in an air atmosphere at 400-500 °C for 30-60 minutes to obtain an inverted battery framework composed of a high-quality planar hole transport layer, a mesoscopic ZrO2 insulating framework layer, and a mesoscopic electron transport layer. Utilizing the structural characteristics of this inverted battery framework, the three-dimensional FAPbI3 light-absorbing layer filled in the mesoscopic insulating framework layer can be completely preserved. Simultaneously, the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer in the mesoscopic electron transport layer is transformed into a two-dimensional perovskite layer with a thickness of 100-250 nm, which is 10 times the thickness of the two-dimensional perovskite in traditional two-dimensional / three-dimensional perovskite devices, thus fundamentally improving device stability. Meanwhile, the unconverted portion of FAPbI3 in the mesoscopic electron transport layer can fully contact the electron transport layer, forming a good electron transport channel and achieving high photoelectric conversion efficiency.
[0030] This ingenious device structure design can make full use of the two-dimensional perovskite layer to improve stability without hindering electron extraction and transport. This three-dimensional two-dimensional gradient structure can ensure that the inverted perovskite solar cell achieves high photoelectric conversion efficiency and good long-term stability.
[0031] II. Performance Testing This invention discloses a gradient structure inverted perovskite solar cell. It fully utilizes the structural characteristics of the inverted cell framework, completely preserving the FAPbI3 three-dimensional perovskite light-absorbing layer within the mesoscopic ZrO2 insulating framework layer, and maintaining its excellent contact interface with the mesoscopic electron transport layer. Simultaneously, the electron transport layer, sintered at high temperature, possesses excellent electron transport capabilities, and the (PEA)2PbI4 two-dimensional perovskite filling its pores does not hinder electron transport, thus enabling the inverted cell to achieve high efficiency and good long-term stability. The prepared 1 cm... 2 The efficiency of FAPbI3 / (PEA)2PbI4 gradient structure inverted perovskite solar cells reaches 24.5%~25.5%.
[0032] Test method: Current density-voltage (V) of inverted perovskite solar cells J-V The characteristic curve test was conducted using a solar simulator (SS-F5-3A, manufactured by Kuang Yen Technology, Taiwan) equipped with a Keithley 2400 digital source meter. The light source was set to the standard AM 1.5G solar spectrum with a light intensity of 100 mW·cm². -2 Before each test, the simulator's light intensity is precisely calibrated using a certified standard silicon reference cell, and the irradiance is confirmed using a calibration spectrometer. J-V The curve scanning range was set to -0.1V to 1.2V, with a forward scan (-0.1V→1.2V). During the test, the device electrodes were reversed, the voltage step size was set to 20 mV, and the delay time was 10 ms.
[0033] Long-term stability data are obtained by testing the photoelectric conversion efficiency of the device after it has been exposed to standard simulated sunlight for 1000 hours, and then comparing it with the initial efficiency to calculate the percentage.
[0034] Test data: The following shows 5 sets of data that passed. J-V The open-circuit voltage obtained by the test ( V oc ), short-circuit current ( J sc ), fill factor ( FFThe test results, including photoelectric conversion efficiency (PCE) data, are shown in Table 1 below. Furthermore, the device group maintained 95% of its initial efficiency after 1000 hours of continuous exposure to standard simulated sunlight.
[0035] Table 1. Device in Example 1 passes... J-V The four photoelectric performance parameters obtained from the test
[0036] As shown in Table 1 above, the four key parameters of the battery's photoelectric performance fluctuate within a very narrow range, with the open-circuit voltage remaining stable at 1.19 V and the short-circuit current ranging from 24.85 to 25.49 mA·cm⁻¹. -2 With slight fluctuations in the range, the fill factor reached a very high value (>83%), resulting in a photoelectric conversion efficiency exceeding 24.50%, reaching a maximum of 25.38%. This demonstrates high photoelectric conversion efficiency, good repeatability, and excellent long-term stability, indicating that this technical solution is an effective way to obtain high-efficiency and stable perovskite solar cells.
[0037] Example 2 I. Preparation This invention discloses a method for fabricating a gradient structure inverted perovskite solar cell, comprising the following steps: Step 1: Prepare a 2.5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 200℃ for 12 hours, cool it naturally to room temperature, centrifuge it at 8000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm ZrO2 mesoporous hollow microspheres.
[0038] Step 2: Disperse SnO2 nanorods with a particle size of 2 nm, an aspect ratio of 4, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 6 mg / mL. Using a high-shear emulsifier with stirring at 18,000 rpm, slowly add 10 times the volume of ethanol / isopropanol (volume ratio 1:4) as an antisolvent to the dispersion to cause the SnO2 nanorods to aggregate and form microsphere precipitates. Centrifuge at 8,000 rpm for 30 minutes and collect the centrifuged material. Add 10 times the volume of NOBF4 acetonitrile solution (concentration 10 mg / mL) to the centrifuged material and let stand for 24 hours to remove the oleylamine ligands on the surface of the nanorods, allowing the nanorods to further aggregate and form stable mesoporous microspheres. Centrifuge again at 6,000 rpm for 30 minutes and collect the centrifuged material to obtain 100 nm SnO2 mesoporous microspheres.
[0039] Step 3: Disperse NiO nanocrystals with an oleylamine ligand and a particle size of 3.6 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2 mg / mL; spin-coat the dispersion onto a conductive glass conductive layer using a two-step spin-coating method: first spin-coat at 500 rpm for 10 s to allow the dispersion to fully spread and wet the conductive layer, and then spin-coat at 4000 rpm for 50 s to control the thickness of the NiO nanocrystal layer; then, dry the layer by heating at 100℃ for 30 minutes.
[0040] Step 4: Disperse the 150 nm ZrO2 mesoporous hollow microspheres prepared in Step 1 in anhydrous ethanol / isopropanol (volume ratio 1:4) to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 250 mg / mL; spin-coat the dispersion onto the NiO nanocrystal particle layer using a two-step spin-coating method: first spin-coat at 800 rpm for 10 s to allow the dispersion to spread fully, and then spin-coat at 2000 rpm for 60 s to control the thickness of the ZrO2 mesoporous hollow microsphere layer; then, heat at 100 ℃ for 30 minutes to dry.
[0041] Step 5: Disperse the 100 nm SnO2 mesoporous microspheres prepared in Step 2 in anhydrous ethanol / isopropanol (volume ratio 5:1) to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 100 mg / mL. Spin-coat the dispersion onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method: first spin-coat at 800 rpm for 5-15 s to allow the dispersion to spread fully, then spin-coat at 3000 rpm for 60 s to control the thickness of the SnO2 mesoporous microsphere layer. Afterward, heat at 100 ℃ for 30 minutes to dry. Finally, sinter the sample at 450 ℃ in an atmosphere for 60 minutes to obtain an inverse battery framework consisting of a planar hole transport layer (20 nm), a mesoscopic ZrO2 insulating framework layer (800 nm), and a mesoscopic electron transport layer (300 nm) sequentially stacked on a conductive glass conductive layer.
[0042] Step 6: Prepare the FAPbI3 perovskite light-absorbing layer precursor solution (solute concentrations: FAI 0.98 M, PbI2 1.08 M, FACl 0.06 M; solvent: N,N-dimethylformamide / dimethyl sulfoxide, volume ratio 4:1). Spin-coat the FAPbI3 perovskite light-absorbing layer precursor solution into the mesopores of the ZrO2 insulating framework layer and the mesostructure electron transport layer within the inverted battery framework prepared in Step 5 at 10000 rpm until completely filled. Prepare a 3 mg / mL chlorobenzene solution of p-fluorophenylethyl ammonium iodide (p-FPEAI). During spin-coating at 4000 rpm, drop 30 mL of this solution into the mesostructure electron transport layer filled with the FAPbI3 precursor solution. The upper half of the FAPbI3 filling was converted to (p-FPEA)2PbI4. Then, it was annealed at 150℃ for 20 minutes to generate a three-dimensional / two-dimensional gradient perovskite light absorption layer of FAPbI3 / (p-FPEA)2PbI4, in which the thickness of the FAPbI3 three-dimensional perovskite was 850 nm and the thickness of the (PEA)2PbI4 two-dimensional perovskite layer was 150 nm. After the sample was cooled to room temperature, anhydrous isopropanol was added dropwise at 6000 rpm for 10 s to completely remove the (PEA)2PbI4 two-dimensional perovskite layer covering the upper surface of the mesoscopic electron transport layer, so that the exposed electron transport layer thickness reached 50 nm. Finally, AZO was sputtered at low temperature to ensure that the upper surface of the electron transport layer was in full contact with the AZO electrode, thus obtaining a gradient structure inverse perovskite solar cell.
[0043] II. Performance Testing This invention discloses a gradient-structured inverted perovskite solar cell. Unlike traditional methods that modify ultrathin two-dimensional perovskites (several nanometers or even sub-nanometers), this invention utilizes a specially structured inverted cell framework to generate tens to hundreds of nanometers of two-dimensional perovskite within a mesoporous electron transport layer. This significantly enhances the protection of the three-dimensional perovskite while maintaining the photoelectric conversion, electron extraction, and transport capabilities of the inverted cell. The introduction of (p-FPEA)₂PbI₄ two-dimensional perovskite, which exhibits better hydrophobicity, greatly improves the hydrothermal stability of the inverted cell. The prepared 1 cm⁻¹… 2 The efficiency of FAPbI3 / (p-FPEA)2PbI4 gradient structure inverted perovskite solar cells is 24.5%~25.5%.
[0044] Test method: Inverted perovskite solar cells J-V Characteristic curve testing was performed using a solar simulator (SS-F5-3A, manufactured by Kuang Yen Technology, Taiwan) equipped with a Keithley 2400 digital source meter. The light source was set to the standard AM 1.5G solar spectrum with a light intensity of 100 mW·cm². -2Before each test, the simulator's light intensity is precisely calibrated using a certified standard silicon reference cell, and the irradiance is confirmed using a calibration spectrometer. J-V The curve scanning range was set to -0.1V to 1.2V, with a forward scan (-0.1V→1.2V). During the test, the device electrodes were reversed, the voltage step size was set to 20 mV, and the delay time was 10 ms.
[0045] Long-term stability data are obtained by testing the photoelectric conversion efficiency of the device after it has been exposed to standard simulated sunlight for 1000 hours, and then comparing it with the initial efficiency to calculate the percentage.
[0046] Test data: The following shows 5 sets of data that passed. J-V Test results V oc 、J sc , FF And PCE data. The test results are shown in Table 2 below. Meanwhile, the efficiency of this group of devices remains at 97% of its initial value after 1000 hours of continuous exposure to standard simulated sunlight.
[0047] Table 2. Devices in Example 2 pass... J-V The four photoelectric performance parameters obtained from the test
[0048] As shown in Table 2 above, in Example 2, each device maintains a very stable and high open-circuit voltage (1.20 V) and a short-circuit current >24.50 mA·cm. -2 The highest value reached 25.55 mA·cm -2 The fill factor is >82.5%, the photoelectric conversion efficiency is >24.50%, and the overall performance is stable, with the photoelectric conversion efficiency of group C reaching as high as 25.35%. Therefore, the cells in this embodiment exhibit high photoelectric conversion efficiency, good repeatability, and excellent long-term stability, indicating that this technical solution is an effective way to obtain high-efficiency and stable perovskite solar cells.
[0049] Comparative Example 1 Compared with Example 1, Comparative Example 1 filled the battery skeleton with FAPbI3 three-dimensional perovskite light-absorbing material, and retained the complete FAPbI3 layer in the mesoscopic electron transport layer, that is, it did not convert the upper 1 / 3 to 1 / 2 of it into two-dimensional perovskite, and there was no three-dimensional two-dimensional gradient structure.
[0050] I. Preparation This comparative example demonstrates the fabrication of an inverted perovskite solar cell with a battery framework filled by pure three-dimensional FAPbI3 perovskite light-absorbing material, comprising the following steps: Step 1: Prepare a 2.5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 200℃ for 12 hours, cool it naturally to room temperature, centrifuge it at 8000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm ZrO2 mesoporous hollow microspheres.
[0051] Step 2: Disperse SnO2 nanorods with a particle size of 4 nm, an aspect ratio of 4, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 10 mg / mL. Using a high-shear emulsifier with stirring at 13,000 rpm, 8 times the volume of ethanol / isopropanol (volume ratio 1:1) antisolvent was slowly added dropwise to the dispersion to cause SnO2 nanorods to aggregate and form microsphere precipitates. The precipitate was then centrifuged at 6,000 rpm for 30 minutes and collected. Add 6 times the volume of the centrifuged material to NOBF4 acetonitrile solution (concentration of 10 mg / mL), let stand for 24 hours to remove the oleamine ligands on the surface of the nanorods, allowing the nanorods to further aggregate and form stable mesoporous microspheres. Then centrifuge at 6000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm SnO2 mesoporous microspheres.
[0052] Step 3: Disperse NiO nanocrystals with an oil amine ligand and a particle size of 3.6 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2 mg / mL. The dispersion was spin-coated onto a conductive glass conductive layer in two steps: first, spin-coating at 500 rpm for 10 s to allow the dispersion to fully spread and wet the conductive glass conductive layer; then, spin-coating at 4000 rpm for 50 s to control the thickness of the NiO nanocrystalline particle layer; afterwards, it was dried by heating at 100℃ for 30 minutes.
[0053] Step 4: Disperse the ZrO2 mesoporous hollow microspheres with a particle size of 150 nm prepared in step 1 in anhydrous ethanol / isopropanol (volume ratio 1:1) to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 200 mg / mL. The dispersion was spin-coated onto the NiO nanocrystalline particle layer in step 3 using a two-step spin-coating process. First, the dispersion was spin-coated at 800 rpm for 10 s to allow it to spread fully. Then, it was spin-coated at 3000 rpm for 60 s to control the thickness of the ZrO2 mesoporous hollow microsphere layer. After that, it was dried by heating at 100 ℃ for 30 minutes.
[0054] Step 5: Disperse the SnO2 mesoporous microspheres with a particle size of 150 nm prepared in step 2 in anhydrous ethanol / isopropanol (volume ratio 1:1) to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 150 mg / mL. The dispersion was spin-coated onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method. First, the dispersion was spin-coated at 800 rpm for 5 seconds to allow it to spread fully, and then at 3000 rpm for 60 seconds to control the thickness of the SnO2 mesoporous microsphere layer. Then, place it at 100℃ for 30 minutes to dry; Finally, the sample was sintered at 450°C in air for 60 minutes to obtain an inverted battery skeleton consisting of a planar hole transport layer (20 nm), a mesoscopic ZrO2 insulating framework layer (700 nm), and a mesoscopic electron transport layer (500 nm) sequentially stacked on a conductive glass conductive layer.
[0055] Step 6: Prepare the FAPbI3 perovskite light absorption layer precursor solution (solute concentrations: FAI 0.98 M, PbI2 1.08 M, FACl 0.06 M; solvent: N,N-dimethylformamide / dimethyl sulfoxide, volume ratio 4:1). Spin-coat the FAPbI3 perovskite light absorption layer precursor solution into the mesopores of the ZrO2 insulating framework layer and the electron transport layer of the inverted battery framework prepared in Step 5 at a speed of 10,000 rpm until completely filled. After the sample was cooled to room temperature, anhydrous isopropanol was added dropwise at 6000 rpm for 10 s to completely remove the FAPbI3 three-dimensional perovskite layer covering the upper surface of the mesoscopic electron transport layer, so that the thickness of the exposed electron transport layer reached 50 nm. Finally, AZO was sputtered at low temperature to ensure that the upper surface of the electron transport layer was in full contact with the AZO electrode, thus obtaining a gradient structure inverted perovskite solar cell.
[0056] II. Performance Testing This comparative example fully utilizes the structural characteristics of the inverted battery framework, completely filling the mesoscopic ZrO2 insulating framework layer and the mesoscopic electron transport layer with FAPbI3 three-dimensional perovskite; leveraging the excellent electron transport capability of the high-temperature sintered electron transport layer, the inverted battery achieves high efficiency. The prepared 1 cm 2 The efficiency of inverted perovskite solar cells reaches 23%~24%.
[0057] Test method: Inverted perovskite solar cells J-V Characteristic curve testing was performed using a solar simulator (SS-F5-3A, manufactured by Kuang Yen Technology, Taiwan) equipped with a Keithley 2400 digital source meter. The light source was set to the standard AM 1.5G solar spectrum with a light intensity of 100 mW·cm². -2 Before each test, the simulator's light intensity is precisely calibrated using a certified standard silicon reference cell, and the irradiance is confirmed using a calibration spectrometer. J-VThe curve scanning range was set to -0.1V to 1.2V, with a forward scan (-0.1V→1.2V). During the test, the device electrodes were reversed, the voltage step size was set to 20 mV, and the delay time was 10 ms.
[0058] Long-term stability data are obtained by testing the photoelectric conversion efficiency of the device after it has been exposed to standard simulated sunlight for 1000 hours, and then comparing it with the initial efficiency to calculate the percentage.
[0059] Test data: The following shows 5 sets of data that passed. J-V Test results V oc 、J sc , FF And PCE. The test results are shown in Table 3 below. Meanwhile, after 1000 hours of continuous exposure to standard simulated sunlight, the efficiency of this group of devices remains at 88% of its initial value.
[0060] Table 3 Comparative Example 1 Device in J-V Four photoelectric performance parameters obtained in the test
[0061] As shown in Table 3 above, among the five data sets, the open-circuit voltage of four sets (ABCD) remained at 1.18 V, and the short-circuit current was >24.50 mA·cm. -2 The fill factor is >81%, the photoelectric conversion efficiency is >23.50%, and the overall performance is stable. The fill factor of Group E deviates slightly from 80%, but the voltage and current are slightly improved, and the photoelectric conversion efficiency is close to 23.50%, within a reasonable fluctuation range. Therefore, thanks to the high-temperature sintered cell framework mesoscopic structure and good carrier transport performance, this comparative cell exhibits high photoelectric conversion efficiency and good repeatability. However, due to the lack of two-dimensional perovskite self-encapsulation and interface passivation, the long-term stability data of this group of devices (efficiency maintained at 88% of the initial value after 1000 hours of continuous exposure to standard simulated sunlight) is not as good as the data of the examples (the devices of Examples 1 and 2, under the same test conditions, maintained 95% and 97% of the initial value, respectively). This indicates that the technical solution of this invention patent is an effective way to prepare inverted perovskite solar cells with both high efficiency and high stability.
[0062] Comparative Example 2 Compared with Example 2, Comparative Example 2 completely transformed the FAPbI3 layer filled in the mesoscopic electron transport layer into a two-dimensional perovskite, so that the mesoscopic electron transport layer was completely filled with two-dimensional perovskite.
[0063] I. Preparation This comparative example demonstrates the fabrication of an inverse perovskite solar cell with a mesoscopic electron transport layer completely filled by pure two-dimensional perovskite, comprising the following steps: Step 1: Prepare a 2.5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 200℃ for 12 hours, cool it naturally to room temperature, centrifuge it at 8000 rpm for 30 minutes, collect the centrifuged material, and obtain 150 nm ZrO2 mesoporous hollow microspheres.
[0064] Step 2: Disperse SnO2 nanorods with a particle size of 2 nm, an aspect ratio of 4, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 6 mg / mL. Using a high-shear emulsifier with stirring at 18,000 rpm, slowly add 10 times the volume of ethanol / isopropanol (volume ratio 1:4) as an antisolvent to the dispersion to cause the SnO2 nanorods to aggregate and form microsphere precipitates. Centrifuge at 8,000 rpm for 30 minutes and collect the centrifuged material. Add 10 times the volume of NOBF4 acetonitrile solution (concentration 10 mg / mL) to the centrifuged material and let stand for 24 hours to remove the oleylamine ligands on the surface of the nanorods, allowing the nanorods to further aggregate and form stable mesoporous microspheres. Centrifuge again at 6,000 rpm for 30 minutes and collect the centrifuged material to obtain 100 nm SnO2 mesoporous microspheres.
[0065] Step 3: Disperse NiO nanocrystals with an oleylamine ligand and a particle size of 3.6 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2 mg / mL; spin-coat the dispersion onto a conductive glass conductive layer using a two-step spin-coating method: first spin-coat at 500 rpm for 10 s to allow the dispersion to fully spread and wet the conductive layer, and then spin-coat at 4000 rpm for 50 s to control the thickness of the NiO nanocrystal layer; then, dry the layer by heating at 100℃ for 30 minutes.
[0066] Step 4: Disperse the 150 nm ZrO2 mesoporous hollow microspheres prepared in Step 1 in anhydrous ethanol / isopropanol (volume ratio 1:4) to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 250 mg / mL; spin-coat the dispersion onto the NiO nanocrystal particle layer using a two-step spin-coating method: first spin-coat at 800 rpm for 10 s to allow the dispersion to spread fully, and then spin-coat at 2000 rpm for 60 s to control the thickness of the ZrO2 mesoporous hollow microsphere layer; then, heat at 100 ℃ for 30 minutes to dry.
[0067] Step 5: Disperse the 100 nm SnO2 mesoporous microspheres prepared in Step 2 in anhydrous ethanol / isopropanol (volume ratio 5:1) to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 100 mg / mL. Spin-coat the dispersion onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method: first spin-coat at 800 rpm for 5-15 s to allow the dispersion to spread fully, then spin-coat at 3000 rpm for 60 s to control the thickness of the SnO2 mesoporous microsphere layer. Afterward, heat at 100 ℃ for 30 minutes to dry. Finally, sinter the sample at 450 ℃ in an atmosphere for 60 minutes to obtain an inverse battery framework consisting of a planar hole transport layer (20 nm), a mesoscopic ZrO2 insulating framework layer (800 nm), and a mesoscopic electron transport layer (300 nm) sequentially stacked on a conductive glass conductive layer.
[0068] Step 6: Prepare the FAPbI3 perovskite light absorption layer precursor solution (solute concentrations: FAI 0.98 M, PbI2 1.08 M, FACl 0.06 M; solvent: N,N-dimethylformamide / dimethyl sulfoxide, volume ratio 4:1). Spin-coat the FAPbI3 perovskite light absorption layer precursor solution into the mesopores of the ZrO2 insulating framework layer and the mesopore electron transport layer within the inverted battery framework prepared in Step 5 at 10000 rpm until completely filled. Prepare a 6 mg / mL p-FPEAI chlorobenzene solution. During spin-coating at 2000 rpm, drop this solution onto the mesopore electron transport layer filled with the FAPbI3 precursor solution for 30 s, converting 100% of the FAPbI3 filled within it to (p-FPEA)2PbI4. Then, at 150°C... Annealing at ℃ for 20 minutes yielded a three-dimensional / two-dimensional gradient perovskite light-absorbing layer of FAPbI3 / (p-FPEA)2PbI4, with the FAPbI3 three-dimensional perovskite layer having a thickness of 800 nm and the (PEA)2PbI4 two-dimensional perovskite layer having a thickness of 300 nm. After cooling the sample to room temperature, anhydrous isopropanol was added dropwise at 6000 rpm for 10 s to completely remove the (PEA)2PbI4 two-dimensional perovskite layer covering the upper surface of the mesoscopic electron transport layer, resulting in an exposed electron transport layer thickness of 50 nm. Finally, AZO was sputtered at low temperature to ensure full contact between the upper surface of the electron transport layer and the AZO electrode, thus obtaining a gradient structure inverted perovskite solar cell.
[0069] II. Performance Testing In this comparative example, the FAPbI3 three-dimensional perovskite filling the mesoscopic electron transport layer was 100% transformed into a two-dimensional perovskite. Although the electron transport layer, after high-temperature sintering, possesses excellent electron transport capabilities, its interfacial contact with the FAPbI3 three-dimensional perovskite light-absorbing layer is severely blocked by the two-dimensional perovskite. The resulting 1 cm... 2Inverted perovskite solar cells have no measurable efficiency and cannot complete the photoelectric conversion process.
[0070] Test method: Inverted perovskite solar cells J-V Characteristic curve testing was performed using a solar simulator (SS-F5-3A, manufactured by Kuang Yen Technology, Taiwan) equipped with a Keithley 2400 digital source meter. The light source was set to the standard AM 1.5G solar spectrum with a light intensity of 100 mW·cm². -2 Before each test, the simulator's light intensity is precisely calibrated using a certified standard silicon reference cell, and the irradiance is confirmed using a calibration spectrometer. J-V The curve scanning range was set to -0.1V to 1.2V, with a forward scan (-0.1V→1.2V). During the test, the device electrodes were reversed, the voltage step size was set to 20 mV, and the delay time was 10 ms.
[0071] Long-term stability data are obtained by testing the photoelectric conversion efficiency of the device after it has been exposed to standard simulated sunlight for 1000 hours, and then comparing it with the initial efficiency to calculate the percentage.
[0072] Test data: Comparative Example 2: Due to the severe blockage of electron extraction by the two-dimensional perovskite completely filled in the mesoscopic electron transport layer, the photoelectric performance of the battery failed, and photoelectric performance data could not be obtained.
[0073] The above embodiments and accompanying drawings are not intended to limit the product form and preparation method of the present invention. Any appropriate changes or modifications made by those skilled in the art should be considered as not departing from the patent scope of the present invention.
Claims
1. A method for fabricating gradient structure inverted perovskite solar cells, characterized in that, Includes the following steps: Step 1: Prepare a 1.5-5 mg / mL zirconium dichloroethylene acetone solution, transfer it to a high-pressure reactor with a polytetrafluoroethylene liner, heat it at 180-200℃ for 6-12 hours, cool it naturally to room temperature, centrifuge it at 6000-10000 rpm for 15-30 minutes, collect the centrifuged material, and obtain 100-200 nm ZrO2 mesoporous hollow microspheres; Step 2: Disperse SnO2 nanorods with a particle size of 2-4 nm, an aspect ratio of 3-5, and containing oleylamine ligands in toluene to prepare a SnO2 nanorod dispersion with a concentration of 5-10 mg / mL. Using a high-shear emulsifier with stirring at 10,000 to 20,000 rpm, 4 to 10 times the volume of the ethanol / isopropanol antisolvent is added dropwise to the dispersion to aggregate SnO2 nanorods and form microsphere precipitates. The volume ratio of ethanol to isopropanol in the ethanol / isopropanol antisolvent is 1:1 to 1:
4. Centrifuge at 4000-8000 rpm for 15-30 minutes and collect the centrifuged material; Add 5-10 times the volume of the centrifuged material to a NOBF4 acetonitrile solution, wherein the NOBF4 concentration of the NOBF4 acetonitrile solution is 5-10 mg / mL. Let stand for 12-24 hours to remove the oleamine ligands on the surface of the SnO2 nanorods, further aggregating the nanorods to form stable mesoporous microspheres. Then centrifuge at 4000-8000 rpm for 15-30 minutes, collect the centrifuged material, and obtain 100-150 nm SnO2 mesoporous microspheres. Step 3: Disperse NiO nanocrystals with an oil amine ligand and a particle size of 3-5 nm in n-hexane to prepare a NiO nanocrystal dispersion with a concentration of 2-8 mg / mL. The dispersion was spin-coated onto the conductive layer of conductive glass in two steps. First, the dispersion was spin-coated at 400-800 rpm for 5-10 seconds to allow it to spread and wet the conductive layer. Then, the dispersion was spin-coated at 3000-5000 rpm for 30-60 seconds to control the thickness of the NiO nanocrystalline particle layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Step 4: Disperse the ZrO2 mesoporous hollow microspheres with a particle size of 100~200 nm prepared in Step 1 in anhydrous ethanol / isopropanol with a volume ratio of 1:1~5:1 to prepare a ZrO2 mesoporous hollow microsphere dispersion with a concentration of 100~250 mg / mL. The dispersion was spin-coated onto the NiO nanocrystalline particle layer in two steps. First, the dispersion was spin-coated at 400-800 rpm for 5-15 seconds to allow it to spread fully. Then, the dispersion was spin-coated at 1500-3000 rpm for 30-60 seconds to control the thickness of the ZrO2 mesoporous hollow microsphere layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Step 5: Disperse the SnO2 mesoporous microspheres with a particle size of 100~150 nm prepared in step 2 in anhydrous ethanol / isopropanol with a volume ratio of 1:1~5:1 to prepare a SnO2 mesoporous microsphere dispersion with a concentration of 100~150 mg / mL. The dispersion was spin-coated onto a ZrO2 mesoporous hollow microsphere layer using a two-step spin-coating method. First, the dispersion was spin-coated at 400-800 rpm for 5-15 seconds to allow it to spread fully. Then, the dispersion was spin-coated at 3000-5000 rpm for 30-60 seconds to control the thickness of the SnO2 mesoporous microsphere layer. Then, heat at 100~200℃ for 15~30 minutes to dry; Finally, the sample was sintered in an air atmosphere at 400~500 °C for 30~60 minutes to obtain an inverted battery skeleton in which a hole transport layer, a ZrO2 insulating framework layer and an electron transport layer are sequentially stacked on a conductive glass conductive layer. The thickness of the hole transport layer is 15~25 nm, the thickness of the ZrO2 insulating framework layer is 0.5~1 μm, and the thickness of the electron transport layer is 300~500 nm. Step 6: At a rotation speed of 8000~12000 rpm, spin-coat the FAPbI3 perovskite light-absorbing layer precursor solution into the mesopores of the ZrO2 insulating framework layer and electron transport layer within the inverted battery framework prepared in Step 5. Dissolve phenylethylammonium or 4-fluorophenylethylammonium organic macrocations in chlorobenzene. During the spin-coating antisolvent-induced crystallization process, FA in the upper 1 / 3~1 / 2 region of the FAPbI3 layer within the electron transport layer... + Ion substitution followed by annealing at 100-150 °C for 10-30 minutes yields a three-dimensional two-dimensional gradient perovskite light-absorbing layer with FAPbI3 / (PEA)2PbI4 structure. Finally, an AZO top electrode was sputtered onto the electron transport layer to obtain a gradient structure inverted perovskite solar cell.
2. The method for fabricating gradient structure inverted perovskite solar cells according to claim 1, characterized in that: The device includes a conductive glass conductive layer, and a planar hole transport layer, an insulating frame layer, and an electron transport layer sequentially stacked on the conductive glass conductive layer. The hole transport layer is a planar hole transport layer, the insulating frame layer is a mesoscopic insulating frame layer, and the electron transport layer is a mesoscopic electron transport layer. The planar hole transport layer, the mesoscopic insulating frame layer, and the mesoscopic electron transport layer together constitute a reverse battery skeleton. FAPbI3 three-dimensional perovskite is filled in the inverted battery skeleton; the upper 1 / 3 to 1 / 2 region of the FAPbI3 layer filled in the electron transport layer is transformed into two-dimensional perovskite to form a three-dimensional two-dimensional gradient structure perovskite light absorption layer. The three-dimensional two-dimensional gradient structure perovskite light absorption layer is a FAPbI3 / (PEA)2PbI4 three-dimensional two-dimensional gradient structure perovskite light absorption layer. An AZO top electrode is sputtered onto the electron transport layer to obtain a gradient structure inverted perovskite solar cell.
3. The method for fabricating gradient structure inverted perovskite solar cells according to claim 2, characterized in that: The hole transport layer is prepared from NiO nanocrystals of 3-5 nm, and the hole transport layer is a NiO nanocrystal hole transport layer. The mesoscopic insulating framework layer is prepared from ZrO2 mesoporous hollow microspheres of 100-200 nm. The electron transport layer is prepared from SnO2 nanorods of 2-4 nm in diameter and aspect ratio of 3-5 through self-assembly to form 100-250 nm mesoporous microspheres, and the electron transport layer is a SnO2 nanorod electron transport layer.
4. The method for preparing a gradient structure inverted perovskite solar cell according to claim 2, characterized in that: The three-dimensional two-dimensional gradient structure perovskite light-absorbing layer is replaced by organic large cations that replace the FAPbI3 layer in the upper 1 / 3 to 1 / 2 region of the electron transport layer. + Ions generate a two-dimensional perovskite, which forms a gradient structure with the FAPbI3 three-dimensional perovskite filling the insulating framework layer.
5. A method for fabricating gradient structure inverted perovskite solar cells according to claim 4, characterized in that: The organic macrocation is phenylethylammonium or 4-fluorophenylethylammonium.
Citation Information
Patent Citations
Mesoscopic perovskite solar cell based on chiral perovskite heterojunction and preparation method thereof
CN119053210A
Perovskite battery monomer, perovskite battery pack and preparation method and application of perovskite battery monomer and perovskite battery pack
CN119855349A
All-inorganic perovskite solar cell with double-mesostructure and preparation method of all-inorganic perovskite solar cell
CN122373463A